2009
DOI: 10.1109/tia.2009.2013569
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion Drive Models for Full Electric Marine Propulsion Systems

Abstract: Integrated full electric propulsion systems are being introduced across both civil and military marine sectors. Standard power system analysis packages cover electrical and electromagnetic components but have limited models of mechanical subsystems and their controllers. Hence, electromechanical system interactions between the prime movers, power network, and driven loads are poorly understood. This paper reviews available models of the propulsion drive system components: the power converter, motor, propeller,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…is propulsion method abandons the traditional way in which the shaft system and propeller are driven by the prime mover and is efficient and energy saving and allows excellent maneuverability and flexible arrangements [22,23]. e most common electric propulsion system is generally powered by diesel generator sets, which provide electric power to propulsion motors through switchboard and frequency converters and which then drives the propellers to generate thrust.…”
Section: A Simulation Model For a Marine Electric Propulsionmentioning
confidence: 99%
“…is propulsion method abandons the traditional way in which the shaft system and propeller are driven by the prime mover and is efficient and energy saving and allows excellent maneuverability and flexible arrangements [22,23]. e most common electric propulsion system is generally powered by diesel generator sets, which provide electric power to propulsion motors through switchboard and frequency converters and which then drives the propellers to generate thrust.…”
Section: A Simulation Model For a Marine Electric Propulsionmentioning
confidence: 99%
“…Therefore, simulation models are used to facilitate the design, system analysis and optimization process in such systems [26]. Priceless research works are reported on the AES modeling [25][26][27][28]; however, these works are based on medium and low range power systems and FC is not considered as the main source of energy. Jaster et al reported a hybrid electric propulsion model that use 150 kW auxiliary FC source that is connected to an AC bus bar.…”
Section: All-electric Ship Driveline Modelmentioning
confidence: 99%
“…However, computational time is the main limiting factor since power electronics inverter and converter models require small modeling step times compared to other sub-systems [26]. Apsley et al proposed to use state-averaged models for the inverters, reduced-order models of the power converters and a hybrid model of the rectifiers to solve issues related to the wide range of modeling time constants [28]. simplified driveline model of an AES consisting of a 1 MW Permanent Magnet Synchronous Motor (PMSM), a PMSM control drive, a three phase Voltage Source Inverter (VSI), a 480 kW Fuel Cell stack and a 144 kWh lithium-ion battery pack are modeled in Simulink using simscape library.…”
Section: All-electric Ship Driveline Modelmentioning
confidence: 99%
“…Compared with others servomotors, the most suitable applications of the six-phase motors are electric, hybrid electric vehicles [1] and ship propulsion [2]. The synchronous reluctance motor is one of highest efficiency and lowest cost motors through the optimal design methods [3,4].…”
Section: Introductionmentioning
confidence: 99%